Effect of managerial ownership and institutional ownership on firm value with enterprise risk management disclosure as moderating variables - Paramartha, I Putu Indra Pradnya; Rasmini, Ni Ketut (International research journal of management, IT and social sciences, 2021)
This study aims to obtain empirical evidence regarding the effect of Enterprise Risk Management (ERM) disclosure on the relationship between managerial ownership, institutional ownership, and firm value. The population in this study were companies listed on the Indonesia Stock Exchange from 2017 to 2019. The sampling technique in this study used non-probability sampling with the purposive sampling method to obtain 53 observation periods as research samples. The data analysis technique used in this research is Moderated Regression Analysis (MRA). The results of the study provide empirical evidence that ERM can strengthen the influence of managerial ownership and institutional ownership on firm value. ERM disclosure has proven to be able to convince investors that the management, who is also the owner of the company, focuses on the survival of the company rather than being opportunistic so that the firm value increases. ERM disclosure also shows that there is an effective institutional presence in the composition of shareholder ownership. Further research can add a research period with a newer year of observation so that the results of this study are more robust.